1995
DOI: 10.1289/ehp.95103s153
|View full text |Cite
|
Sign up to set email alerts
|

Trace metal mobilization in soil by bacterial polymers.

Abstract: Enhanced transport of trace metal in porous media can occur in the presence of a ligand or "carrier" that has a high affinity for binding the pollutant, is dispersed and mobile in the soil environment, is recalcitrant with respect to microbial degradation, and is acceptable to the public. These aspects of the facilitated transport to trace metals are discussed with respect to a naturally occurring carrier: extracellular polymers of bacterial origin. The literature is reviewed regarding the production and compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
1
8
0
1
Order By: Relevance
“…Azotobacter synthesize some biologically active substances, including some phytohormones such as auxins (Ahmad et al, 2005). They also facilitate the mobility of heavy metals in the soil and thus enhance bioremediation of soil form heavy metals, such as cadmium, mercury and lead (Chen et al, 1995). Similar results were also obtained earlier by Rashmi et al, (2007) and Murali et al, (2006) who have established the increased availability of NPK when biofertilizers were integrated with different types of organics.…”
Section: Soil Microbes In the Rhizosphere Of Mulberrysupporting
confidence: 84%
“…Azotobacter synthesize some biologically active substances, including some phytohormones such as auxins (Ahmad et al, 2005). They also facilitate the mobility of heavy metals in the soil and thus enhance bioremediation of soil form heavy metals, such as cadmium, mercury and lead (Chen et al, 1995). Similar results were also obtained earlier by Rashmi et al, (2007) and Murali et al, (2006) who have established the increased availability of NPK when biofertilizers were integrated with different types of organics.…”
Section: Soil Microbes In the Rhizosphere Of Mulberrysupporting
confidence: 84%
“…EPS contributes significantly to the metal‐binding capabilities of exopolymer, as it has been found that EPS has metal‐binding and mobilization properties in aquatic and terrestrial environments (Mittelman and Geesey, 1985; Lion et al ., 1988; Bender et al ., 1994; Chen et al ., 1995a,b; Nelson et al ., 1995; 1996; Puranik and Paknikar, 1999). Toxic metals, such as cadmium and lead, bind to biofilm exopolymers, facilitating metal transport and ameliorating metal toxicity (Mittelman and Geesey, 1985; Lion et al ., 1988; Chen et al ., 1995a; Nelson et al ., 1995; 1996; Xie et al ., 1996; Czajka et al ., 1997). Factors that help to solubilize and mobilize toxic metals in soils are sought after, as desorption and transport can be the limiting factors during metal removal processes (Puranik and Paknikar, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers argued that BEP might act as a potential agent or surfactant for enhancing the remediation efficiency of the contaminated soils in engineered phytoremediation or bioremediation application because BEP exhibited an obvious affinity with heavy metal or hydrophobic organic pollutants. Furthermore, BEP occurs naturally, and application may be more acceptable to the public than the application of synthetic chelating agents or surfactants (Chen et al, 1995a, 1995b; Liu et al, 2001; Dohse and Lion, 1994; Czajka et al, 1997). However, in this study, BEP derived from activated sludge appeared to be of little value in remediating Cu‐contaminated soils because its higher biodegradability and much lower ability to increase Cu uptake by plants than common synthetic chelating agents such as EDTA.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous investigations have revealed that dissolved macromolecules or colloidal particles in soils can act as a potential “carrier” to facilitate the transport of heavy metals through the formation of soluble metal–organic complexes (Lamy et al, 1993; McCarthy et al, 1993), especially for Cu (Temminghoff et al, 1997; Guibaud et al, 2003; Zhou and Wong, 2003). Dissolved macromolecules in soil systems include humic substances and bacterial polymers (Chen et al, 1995a).…”
mentioning
confidence: 99%